Heat reacclimation using exercise or hot water immersion - Gerrett, N.; Alkemade, P.; Daanen, H. (Medicine & Science in Sports & Exercise, 2021)
Introduction: The aim of this study was to compare the effectiveness of exercise versus hot water immersion heat reacclimation (HRA) protocols. Methods: Twenty-four participants completed a heat stress test (HST; 33°C, 65% RH), which involved cycling at a power output equivalent to 1.5 W·kg-1 for 35 min whereby thermophysiological variables were measured. This was followed by a graded exercise test until exhaustion. HST1 was before a 10-d controlled hyperthermia (CH) heat acclimation (HA) protocol and HST2 immediately after. Participants completed HST3 after a 28-d decay period without heat exposure and were then separated into three groups to complete a 5-d HRA protocol: a control group (CH-CON, n = 8); a hot water immersion group (CH-HWI, n = 8), and a controlled hyperthermia group (CH-CH, n = 8). This was followed by HST4. Results: Compared with HST1, time to exhaustion and thermal comfort improved; resting rectal temperature (Tre), end of exercise Tre, and mean skin temperature (Tsk) were lower; and whole body sweat rate (WBSR) was greater in HST2 for all groups (P < 0.05). After a 28-d decay, only WBSR, time to exhaustion, and mean Tsk returned to pre-HA values. Of these decayed variables, only WBSR was reinstated after HRA; the improvement was observed in both the CH-CH and the CH-HWI groups (P < 0.05). Conclusion: The data suggest that HRA protocol may not be necessary for cardiovascular and thermal adaptations within a 28-d decay period, as long as a 10-d CH-HA protocol has successfully induced these physiological adaptations. For sweat adaptations, a 5-d CH or HWI-HRA protocol can reinstate the lost adaptations.